2021
DOI: 10.1002/tafs.10299
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change May Cause Shifts in Growth and Instantaneous Natural Mortality of American Shad Throughout Their Native Range

Abstract: American Shad Alosa sapidissima is an anadromous species with populations ranging along the U.S. Atlantic coast. Past American Shad stock assessments have been data limited and estimating system-specific growth parameters or instantaneous natural mortality (M) was not possible. This precluded system-specific stock assessment and management due to reliance on these parameters for estimating other population dynamics (such as yield per recruit). Furthermore, climate-informed biological reference points remain a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Despite the fact that total available habitat was divided fairly evenly among eco-regions, the relative scope for population size is substantially greater in the NI, decreased in the SI and lowest in the SM ecoregion due to differences in life history. While this is intuitive based on the degree of iteroparity, growth rates, and maximum sizes (Gilligan-Lunda et al, 2021), it highlights the difference between relative and absolute losses of spawner potential due to dams. The SM eco-region's lost scope of 1.74 million fish is dwarfed by the loss of more than 13 million in the NI ecoregion, suggesting that parallel differences in fisheries potential also exist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the fact that total available habitat was divided fairly evenly among eco-regions, the relative scope for population size is substantially greater in the NI, decreased in the SI and lowest in the SM ecoregion due to differences in life history. While this is intuitive based on the degree of iteroparity, growth rates, and maximum sizes (Gilligan-Lunda et al, 2021), it highlights the difference between relative and absolute losses of spawner potential due to dams. The SM eco-region's lost scope of 1.74 million fish is dwarfed by the loss of more than 13 million in the NI ecoregion, suggesting that parallel differences in fisheries potential also exist.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the potential for all 164 rivers to support spawning runs of adult American shad, estimates of spawner potential are directly linked to estimates of available habitat (Figure 7). However, latitudinal variation in growth, maturation, and post-spawn survival (Leggett and Carscadden, 1978;Gilligan-Lunda et al, 2021) all influence the relative differences observed in population potential. On average, a square km of habitat results in 55,200 spawners in the NI eco-region but only 31,000 in the SI eco-region.…”
Section: Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the existing literature, three life cycle processes, i.e. including growth at sea (Gilligan-Lunda et al 2021), survival of spawners , and survival of early-life stages in rivers , were linked to temperature to account for whole-life cycle impacts to global warming ). To assess the potential for shad to deliver nutrients across European river basins, an original nutrient routine providing estimates of nutrient imports and exports was designed and combined with GR3D.…”
Section: Introductionmentioning
confidence: 99%